2014
DOI: 10.1128/aac.01772-13
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Staphylococcal Cassette Chromosomal Element, SCC fusC , Carrying fusC and speG in Fusidic Acid-Resistant Methicillin-Resistant Staphylococcus aureus

Abstract: A high prevalence of fusC (16/46, 59%) was found in fusidic acid-resistant methicillin-resistant Staphylococcus aureus isolates collected from 2008 to 2010. Nucleotide sequencing of fusC and flanking regions revealed a novel staphylococcal cassette chromosome (SCC) structure, SCCfusC, which was integrated into rlmH and located upstream from SCCmec. The SCCfusC element contained speG, which may contribute to the polyamine resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…The cassette in the ST1 isolates (with the exception of MRSA3, see below) was identical to the previously described SCC 476 ( Fig. 2 B; Table 2 ), whereas the cassette that encoded fusC in ST149 was novel compared with both of the previously described fusC -encoding SCC elements (SCC 476 and SCC fusC ) [24,25] .…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The cassette in the ST1 isolates (with the exception of MRSA3, see below) was identical to the previously described SCC 476 ( Fig. 2 B; Table 2 ), whereas the cassette that encoded fusC in ST149 was novel compared with both of the previously described fusC -encoding SCC elements (SCC 476 and SCC fusC ) [24,25] .…”
Section: Resultsmentioning
confidence: 61%
“…Current data suggest recent global spread of fusC MRSA, with an association with the epidemic ST239 clone in Taiwan [25] , and the emergence of diverse fusC MRSA in New Zealand following increased usage of fusidic acid since 2000 [26] . Previous UK data have shown that between 1990 and 2001 annual sales of this drug more than doubled from 1.2 t to 3 t [8] , whilst fusidic acid resistance in MRSA in UK bacteraemia isolates increased from 1.8% to 5.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, fusC has been detected on a novel staphylococcal cassette chromosome (SCC) structure, named SCCfusC, in MRSA strains. It was found upstream of the SCCmec and also included speG, probably mediating polyamine resistance [22]. Further evaluation is needed to clarify the existence of crossresistance for fusidic acid and (molecular) epidemiology of its resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The fusC gene is particularly prevalent among fusidic acid-resistant S. aureus and CoNS strains, and to date, it has always been identified within staphylococcal cassette chromosome (SCC) elements, with or without the mecA gene (139,(142)(143)(144)(145)(146). One recent study assessed the genetic context of fusC across different lineages of S. aureus, including ST5 and ST1 (147).…”
Section: Fusidic Acidmentioning
confidence: 99%